Edge Perpendicular Binary Coding for USM Sharpening Detection - Ding, Feng; Zhu, Guopu; Yang, Jianquan; Xie, Jin; Shi, Yun-Qing (IEEE signal processing letters, 2015)
Unsharp masking (USM) sharpening is a basic technique for image manipulation and editing. In recent years, the detection of USM sharpening has attracted attention from image forensics point of view. After USM sharpening, overshoot artifacts, which shape image texture, are generated along image edges. By utilizing the special characteristic of the texture modification caused by the USM sharpening, a novel method called edge perpendicular binary coding is proposed in this letter to detect USM sharpening. Extensive experiments have been conducted to show the superiority of the proposed method over the existing methods.